Study on the interaction of Prodigiosin with bovine serum albumin by spectroscopic methods. Issue 1 (2012) - Liu Liu, Shu-Chao Shu-Chao; Tang Tang, Jing Jing; Zhang Zhang, Xi-Hai Xi-Hai; Gao Gao, Yuan-Yuan Yuan-Yuan; Ma Ma, Fei Fei; Yang Yang, Qi-yin Qi-yin
Abstract : The interaction between bovine serum albumin (BSA) and Prodigiosin (PG) was investigated by UV-vis absorption, fluorescence, synchronous fluorescence, FT-IR and circular dichroism (CD) techniques. The data of UV-vis absorption and fluorescence spectra displayed that there existed interaction between PG and aromatic amino acid residues of BSA. The synchronous fluorescence and CD spectrum experiment both showed that the secondary structure of BSA changed with addition of PG. All these results revealed that the conformation and microenvironment of BSA were changed.